Measurement of Capital Depreciation within the Japanese Fishing Fleet - Lee, Bun Song (The Review of Economics and Statistics, 1978)
AN important unresolved question in the analysis of capital investment is whether the deterioration of physical capital occurs at a constant exponential rate. (For detailed discussion see both Jorgenson (1971) and Feldstein and Rothschild (1974).) The empirical evidence on physical capital depreciation patterns is inadequate to refute any proposition about the actual decay of capital inputs. On the one hand, analyses of acquisition prices of new and used automobiles by Wykoff (1970) and by Cagan (1965) and of used farm tractors by Griliches (1960) uniformly concluded that the geometric depreciation function adequately characterizes the true depreciation function. On the other hand, Hall (1971) and Feldstein and Rothschild (1974) found statistical grounds for rejecting the null hypothesis of an exponential depreciation function. The major purpose of this paper is to apply the statistical test procedure on the geometric depreciation function developed by Hall (1971) and Jorgenson (1971) to data on Japanese fishing boats. The published Japanese data on the insured value of fishing boats against total loss are adjusted to reflect the assessed market valuation for insurance purposes. These adjusted values are used as proxies for the acquisition prices of new and used fishing boats. These proxy variables can be justified because it is common practice for the insurance companies to minimize the difference between the insured value of capital items and their market or actual replacement value. This is accomplished by annual adjustments of insured values for physical deterioration and technical obsolescence (Lee, 1973). These data form a unique set for comparison with the acquisition price data on used automobiles frequently employed in previous studies. To date, most attention in the literature on capital depreciation has been paid to consumer durables, particularly to automobiles, with the exception of Griliches (1960). By comparison, fishing boats are capital inputs to fishery production activity. In Cagan's (1965) expression, the demand for capital inputs is less likely to be influenced by ephemeral fads and will reflect greater emphasis on innovations of enduring importance than will the demand for consumer durables. In addition, since the assessed market valuation of new boats for insurance purposes is believed to reflect satisfactorily the actual value of new boats, the data should reveal some information on that portion of the lifetime depreciation of a capital asset that takes place during the first year of its life. By contrast, the data constraints of previous studies allowed capital depreciation analyses only for vehicles that were more than one year old. This was an unfortunate and significant omission.' Though the Hall model (1971) is fundamentally under-identified, as will be discussed in detail later, it is still possible to statistically test several typical assumptions regarding the nature of depreciation and embodied technical change that are commonly seen in economic literature. While the results of the test are specific to the Japanese fishing fleet, interpretation of these results along with the results of previous studies should give some indication whether the typical assumptions are empirically Received for publication September 14, 1975. Revision accepted for publication June 23, 1977. * Research Triangle Institute. An earlier version of this paper was presented at the Third World Congress of the Econometric Society, Toronto, Canada, in August 1975. Grateful appreciation is extended to W. Kenneth Poole, Jerome A. Olson, and Allen K. Miedema at Research Triangle Institute for discussion and comments on earlier drafts and to Joanne Turner Rogoff of Research Triangle Institute for her editorial assistance in the preparation of this article. The author also thanks an unknown editorial referee for invaluable comments and criticisms. I Hall (1971) measured the depreciation of half-ton pickup trucks relative to 1-year-old trucks because the prices of new trucks were not available from his sources. Wykoff's (1970) study of acquisition prices of new and used automobiles reveals a sharp drop between the price of new cars and the price of used cars. Jorgenson (1971) contends that Wykoff's finding is attributable mainly to the inadequacy of the list prices of new equipment to reflect the prices paid at actual transactions.